Pengaruh Koneksi Politik Dan Media Exposure Terhadap Pengungkapan Tanggung Jawab Sosial - Anggraini Risky Muliawati; Hariyati Hariyati (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2021)
This study aims to examine and analyze the influence of political connections and media exposure on disclosure of Corporate Social Responsibility (CSR). This research is a quantitative study using secondary data from annual reports and sustainability reports of 195 High Profile companies listed on the Indonesia Stock Exchange (IDX) in 2018-2019. This study uses the dependent variable in the form of CSR disclosure measured by the analytical method adopted from the research of Sembiring (2005). The independent variables in the form of political connections and media exposure are measured using dummy variables. The data analysis technique used is multiple linear regression analysis with SPSS software. The results of this study indicate that there is an influence of political connections and media exposure on disclosure of Corporate Social Responsibility (CSR).